ANALISIS KETERAMPILAN GURU DALAM MENGELOLA KELAS SISWA TUNARUNGU DI SDLB KASIH IBU PEKANBARU - Eka Fauziah; Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research is motivated by the awareness of the importance of applying basic skills to manage classes for deaf students who are not as appropriate. This results in deaf students not being able to get the optimal learning process. This research method uses a qualitative approach with descriptive method. Descriptive learning research aims to find out the application of basic teaching skills in managing classes of deaf students in Extraordinary Elementary Schools. The study was conducted in two classes, namely, the low class and high class with the research subject is the low and high-class teachers. The research data is obtained from observing the teacher's skills in managing the class and interviews with related sources. The results of the study are that the application of basic teaching skills in managing classes for deaf students has been carried out in accordance with the components of classroom management even though they have not met all the indicators of observation. Classroom arrangement has also supported a more optimal classroom management process. Based on the results of these studies, it can be concluded that the implementation of basic teaching skills in managing the class of deaf students at the Extraordinary Elementary School of Love for Pekanbaru Pekanbaru has been done quite well.